Service member and veteran mental distress rates and military-civilian residential segregation in South Carolina counties. Issue 3 (2nd September 2019) - McDaniel, Justin T.; Mayer, Alyssa B.; McDermott, Robert J.; Albright, David L.; Yun Lee, Hee; Harara, Eva
ABSTRACT: We examine service member/veteran (SMV) mental distress rates in South Carolina counties and military-civilian residential segregation (MCRS). In phase one of our analysis, we utilized small area estimation (SAE) via a generalized-linear mixed model (GLMM) to calculate the probability of mental distress rates among SMVs, using individual-level data from the 2017 Behavioral Risk Factor Surveillance System (BRFSS). We applied these probabilities to demographic population counts (i.e. age by race by sex by military status) prepared at the county level by the U.S. Bureau of the Census in order to develop rates of SMV mental distress for each county. In phase two, we used these calculated mental distress rates and block-group-level 2013–2017 five-year American Community Survey (ACS) data to calculate MCRS for counties and to assess the relationship between SMV mental distress rates and MCRS. Phase one results showed that the average predicted mental distress rate among SMVs was 9.33 percent, although we found geographic variation across counties. Phase two results showed that the average mental distress rate was higher in counties with high compared to low MCRS (9.58 vs. 9.22) (Cohen's d = 0.62). Social connection opportunities for SMVs and civilians are needed where high MCRS occurs.